2019
DOI: 10.1038/s41467-019-12557-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple associative structures created by reinforcement and incidental statistical learning mechanisms

Abstract: Learning the structure of the world can be driven by reinforcement but also occurs incidentally through experience. Reinforcement learning theory has provided insight into how prediction errors drive updates in beliefs but less attention has been paid to the knowledge resulting from such learning. Here we contrast associative structures formed through reinforcement and experience of task statistics. BOLD neuroimaging in human volunteers demonstrates rigid representations of rewarded sequences in temporal pole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 80 publications
4
36
0
Order By: Relevance
“…Moreover, the preferential encoding of actor prediction errors by the striatum and dopaminergic midbrain is consistent with earlier findings showing that the mesolimbic pathway preferentially encodes reward prediction errors in instrumental learning tasks (Garrison et al, 2013;Grogan et al, 2020;Hamid et al, 2019;O'Doherty, 2004). Conversely, the preferential encoding of spectator prediction errors by the mPFC is consistent with its more general role in statistical learning (Gilboa and Marlatte, 2017;Klein-Flügge et al, 2019). It may explain why dysfunctions of this structure impair observational learning more profoundly than instrumental learning (Jurado-Parras et al, 2012;Kumaran et al, 2015) and why mPFC lesions can alter the perception of controllability without altering performance of simple instrumental learning tasks (O'Callaghan et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the preferential encoding of actor prediction errors by the striatum and dopaminergic midbrain is consistent with earlier findings showing that the mesolimbic pathway preferentially encodes reward prediction errors in instrumental learning tasks (Garrison et al, 2013;Grogan et al, 2020;Hamid et al, 2019;O'Doherty, 2004). Conversely, the preferential encoding of spectator prediction errors by the mPFC is consistent with its more general role in statistical learning (Gilboa and Marlatte, 2017;Klein-Flügge et al, 2019). It may explain why dysfunctions of this structure impair observational learning more profoundly than instrumental learning (Jurado-Parras et al, 2012;Kumaran et al, 2015) and why mPFC lesions can alter the perception of controllability without altering performance of simple instrumental learning tasks (O'Callaghan et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…As such, our findings suggest that the contribution of OFC to decision making may be limited to situations that require model-based planning, and that choices based on direct experience may rely on value computations in other brain areas, such as the amygdala or striatum (Paton et al, 2006;Cox and Witten, 2019). This proposal is seemingly at odds with a large number of studies across different species that has shown neural correlates of both inferred and directly experienced value in OFC (Hare et al, 2009;Schoenbaum et al, 2009;Barron et al, 2013;Stalnaker et al, 2014;Howard et al, 2015;Padoa-Schioppa and Conen, 2017;Suzuki et al, 2017;Klein-Flugge et al, 2019;Lopez-Persem et al, 2020;Wang et al, 2020). Why would OFC represent value signals if they are not required for behavior?…”
Section: Discussionmentioning
confidence: 72%
“…As such, our findings suggest that the contribution of OFC to decision-making may be limited to situations that require model-based planning, and that choices based on direct experience may rely on value computations in other areas, such as the amygdala or striatum ( Paton et al, 2006 ; Cox and Witten, 2019 ). This proposal is seemingly at odds with the large number of studies across different species that consistently report neural correlates of both inferred and directly experienced value in OFC ( Hare et al, 2009 ; Schoenbaum et al, 2009 ; Barron et al, 2013 ; Stalnaker et al, 2014 ; Howard et al, 2015 ; Padoa-Schioppa and Conen, 2017 ; Suzuki et al, 2017 ; Klein-Flügge et al, 2019 ; Lopez-Persem et al, 2020 ; Wang et al, 2020 ). Why would OFC represent value signals if they are not required for behavior?…”
Section: Discussionmentioning
confidence: 98%